Bibliometric Analysis on Gender and Spirituality in Literary Studies - Thoyib, Muhammmad Edy; Rochman, Chaerul (Universitas Sanata Dharma, 2024)
Publications on gender and spirituality have been prominently featured in many journals indexed by various databases. This article employs bibliometric analysis to investigate publication trends on gender and spiritual issues in literary studies within the Scopus database. This research utilized the VOSviewer application to analyze keyword co-authorship, co-occurrence, and citations. The bibliographic data for this study were downloaded from the Scopus database on January 8, 2024, with a search restriction over the last ten years between 2014 and 2023, and under two fields: 1) social sciences and 2) arts and humanities. The results show that of the 34 eligible publications, there are four main highlights. First, the co-authorship of research publications is relatively low and is only undertaken by a few researchers. Second, the co-occurrence of keywords reveals three main research trends over these ten years: gender-based experiences and practices, gender-based concepts, and religion and spirituality. However, keywords related to literary criticism did not appear. Third, the number of citations for documents is uneven and is dominated only by certain authors, affiliations, and countries. Lastly, network visualization reveals limited interconnectivity between topics, such as gender spirituality and literature. These results conclude that interdisciplinary research in the field of literary criticism remains widely open to address existing research gaps and encourage researchers to collaborate on related topics.